(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The paper attempts to examine the obsolescence of literature inPolitical Science. The study is based on the 1738 citations, cited in the 14doctoral dissertations of Political science awarded from the department ofPolitical Science, Kurukshetra University. Kurukshetra during the period of1998-2007.it is observed that journals and books are the most preferredbibliographic form of citations used by the research scholars, and they occupy37.30% and 38.53% respectively.